1997
DOI: 10.1161/01.cir.96.7.2421
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Purkinje System in Spontaneous Ventricular Tachycardia During Acute Ischemia in a Canine Model

Abstract: In this model, VT with a focal mechanism is commonly seen in the early ischemic period. Sixty percent of the VTs were of focal Purkinje origin as characterized by three-dimensional activation mapping. The results of this study indicate that Purkinje tissue may play an important role in the development of early ischemic VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 21 publications
2
68
0
Order By: Relevance
“…Thus, in phase I A , reentry seems to play a major role in the genesis of the arrhythmia, although focal mechanisms in the Purkinje cells have also been suggested. 29 In phase IB, the mechanism of the arrhythmias is unclear. Although intramural reentry may be involved in their occurrence, the progressive accumulation of catecholamines that occurs in this phase 30 has led us to believe that such neurotransmitters could induce focal mechanisms such as an abnormal automatism.…”
Section: Possible Mechanism Of Ventricular Tachycardiamentioning
confidence: 99%
“…Thus, in phase I A , reentry seems to play a major role in the genesis of the arrhythmia, although focal mechanisms in the Purkinje cells have also been suggested. 29 In phase IB, the mechanism of the arrhythmias is unclear. Although intramural reentry may be involved in their occurrence, the progressive accumulation of catecholamines that occurs in this phase 30 has led us to believe that such neurotransmitters could induce focal mechanisms such as an abnormal automatism.…”
Section: Possible Mechanism Of Ventricular Tachycardiamentioning
confidence: 99%
“…2,3 Studies have demonstrated that the Purkinje fiber system may be responsible for the onset of arrhythmias during post-infarct ischemia and reperfusion, [4][5][6] and that congestive heart failure leads to changes in the Purkinje cells that may make them more prone to arrhythmogenesis. 7 Studies have also suggested that the specialized conduction system may be important in the maintenance of VF.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to use biochemical, immunohistochemical and electrophysiological approaches to investigate whether the skeletal muscle Na V 1.4 is expressed in canine Purkinje single myocytes. Slowly inactivating plateau currents are potential source of arrhythmias and the Purkinje system can be a site of origin of ventricular arrhythmias, such as those that occur in the early ischemic period [12,13].…”
Section: Introductionmentioning
confidence: 99%